Nonpharmacological interventions for decreasing anxiety during anesthesia induction in children: a systematic review and Bayesian network meta-analysis - Yuanyuan Li; Shanshan Peng; Xueqin Xia; Lin Yin; Limei Liao (BMC Anesthesiology)
Abstract Background Anxiety during anesthesia induction can lead to various negative outcomes and psychological burdens in children undergoing surgery. Nonpharmacological interventions are available for reducing anxiety in this context. However, due to a lack of evidence from head-to-head randomized controlled trials (RCTs), the specific effects of these methods on children with anxiety during anesthesia induction remain unclear. Objective This network meta-analysis aimed to evaluate the comparative effects of all known nonpharmacological interventions for reducing anxiety in children during anesthesia induction and to rank these interventions based on their practical applicability. Design Systematic review and Bayesian network meta-analysis. Methods We searched PubMed, Embase, CINAHL, Cochrane Library, and Web of Science to identify articles published up to August 2024. Two reviewers independently assessed eligibility of potential studies and extracted data. Outcome measures of the meta-analysis were the anxiety levels of children during anesthesia induction, the anxiety levels of parents, and the child’s compliance during anesthesia induction. A consistency model was selected to conduct a network meta-analysis to evaluate the relative effects and rank probabilities of different nonpharmacological interventions. Results A total of 34 RCTs with 3,040 participants and six intervention methods were included. All trials confirmed the safety of the six intervention methods, with no significant adverse events reported. The network meta-analysis showed that the Passive Distraction Intervention (PDI)-Parental Presence at Induction of Anesthesia (PPIA), Interactive Distraction Intervention (IDI)-PPIA, IDI, PDI, and PPIA interventions were associated with more substantial reductions in anxiety than usual care. However, the studied interventions showed no statistically significant differences for reducing parental anxiety. The PPIA, IDI, and IDI-PPIA interventions also improved compliance during anesthesia induction. Conclusions Our study confirmed that some nonpharmacological interventions are effective at reducing anxiety in children and enhancing compliance during anesthesia induction. Therefore, we recommend several interventions for clinical practice, including the PDI-PPIA, IDI-PPIA, PDI, IDI, and PPIA when working with children undergoing anesthesia induction. Registration We registered this network meta-analysis with PROSPERO (registration no. CRD42022262874). Clinical trial number Not applicable.